Dual‐task gait and cognitive performance in midlife type 2 diabetes mellitus (T2DM): Baseline data from ENBIND: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Dyer, Adam H; McKenna, Louise; Gamage, Githmi; Killane, Isabelle; Woods, Conor; O'Neill, Desmond; Gibney, James; Bourke, Nollaig; Reilly, Richard; Kennelly, Sean
Abstract: Background: Midlife Type 2 Diabetes Mellitus (T2DM) is associated with an increased risk of dementia in later life. Despite this, few studies have examined the utility of midlife biomarkers to predict later cognitive decline in T2DM. We evaluated the association between dual‐task gait speed and cognitive performance in midlife T2DM as part of ENBIND Study. Method: Participants with midlife T2DM and matched healthy controls were recruited. Participants with T2DM only included if they had no micro/macrovascular complications of T2DM. Cognition was assessed using the Montreal Cognitive Assessment (MoCA) and computerised neuropsychological assessment battery (CANTAB ® ). Gait was assessed using both stopwatch and accelerometry across four tasks: (i) self‐selected (usual) gait speed, (ii) maximal gait speed and (iii) dual‐task gait speed (reciting alternate letters of the alphabet). Appropriate univariate statistics in addition to Poisson and linear models were used to analyse results. Results: 102 cognitively‐intact middle‐aged (52 ± 7.9 years) adults with (N = 71) and without (N = 31) T2DM were recruited. T2DM was associated with a greater likelihood of error on the MoCA (IRR = 2.36, 1.53‐3.64, p<0.001) which persisted after covariate adjustment. T2DM was associated with poorer performance on reaction/movement time, executive function, attention and visuospatial memory tasks, however results were attenuated by covariate adjustment. T2DM was associated with slower gait speed on all three tasks (all p<0.001). Overall, self‐selected, maximal and dual‐task speed were associated with greater likelihood of error on the MoCA (all p<0.001). However, after robust adjustment for covariates, only the association for Dual Task Cost (DTC) persisted (p = 0.021). A DTC*T2DM interaction was not significant. Conclusions: The current analysis showed diminished cognitive and gait performance in midlife T2DM vs. healthy controls. We observed significant associations between gait performance on the addition of a dual task and general cognitive function. This association, whilst greater in T2DM, was not T2DM specific and adds further evidence for the association between dual task‐gait and cognitive performance in midlife. Our findings support the ongoing exploration and use of gait as a physiological biomarker of overall cognitive function and warrants longitudinal investigation in this high risk group.